PENGEMBANGAN KONSEP RINTISAN EDU WISATA DI UKM CITARA DESA BANJARARUM KEC. SINGOSARI KAB. MALANG - Nurhadi, Nurhadi; Wiharya, Chandra; Santoso, Santoso; Listiyono, Listiyono; Walid, Achmad (Universitas Mataram, 2024)
UKM Citara is developing a seaweed processing business and cultivating catfish in bioflock ponds together with community members as a food security effort due to the impact of the Covid 19 pandemic at the beginning of 2020. Several government/private agencies have visited UKM to learn about seaweed processing and bioflock catfish cultivation, including vocational school students/internship students. The problem is that the cultivation area of ​​± 2,000 m has not been utilized optimally and SMEs do not yet have an educational tourism concept for their visitors. The aim of the activity is to optimize land use and design a pilot concept for bioflock fish cultivation tourism. The hope is that the cultivated land will be utilized optimally and there will be educational facilities for other parties who come to UKM. The activity method is creating a tourism edu pilot concept in the form of learning tutorials and exploring places at UKM Citara, creating visual images of tourism edu pilots, installing smart ponds, gazebos, gates and irrigation channels in the UKM Citara bioflock fish farming area. The result of this community service activity is the realization of the concept and realization of a tourism edu pilot for seaweed processing and bioflock fish cultivation at UKM Citara which can improve the functionality of ± 2,000 m of empty land which was originally only used for bioflock fish cultivation, then developed into a tourism edu pilot area. which is useful. Visitors can receive education in the form of tutorials on processing seaweed products and cultivating bioflock fish and can explore seaweed processing and bioflock fish cultivation sites. This activity has increased the use of empty land and realized a pioneering educational tourism concept that needs further development.